2005
DOI: 10.1088/0022-3727/38/22/002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid magnetic hardening by rapid thermal annealing in NdFeB-based nanocomposites

Abstract: A systematic study of heat treatments and magnetic hardening of NdFeB-based melt-spun nanocomposite ribbons have been carried out. Comparison was made between samples treated by rapid thermal annealing and by conventional furnace annealing. Heating rates up to 200 K s −1 were adopted in the rapid thermal processing. It was observed that magnetic hardening can be realized in an annealing time as short as 1 s. Coercivity of 10.2 kOe in the nanocomposites has been obtained by rapid thermal annealing for 1 s, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…The RTA induced magnetic hardening within several seconds for other magnetic materials was also observed and discussed in other reports. [23][24][25] This phenomenon may be explained by a lowered phase transition temperature in RTA treated samples. Figure 5 shows the demagnetization curve of the 8 nm FePt particles annealed at 650°C for 10 s by RTA as an example.…”
Section: Resultsmentioning
confidence: 99%
“…The RTA induced magnetic hardening within several seconds for other magnetic materials was also observed and discussed in other reports. [23][24][25] This phenomenon may be explained by a lowered phase transition temperature in RTA treated samples. Figure 5 shows the demagnetization curve of the 8 nm FePt particles annealed at 650°C for 10 s by RTA as an example.…”
Section: Resultsmentioning
confidence: 99%
“…The inability of the transformation of amorphous into crystalline phase in the present work is attributed to short time (0.2 s) used. A recent investigation reveals that heating time greater than 1 s is required to promote complete crystallization in amorphous NdFeB ribbons and thereby achieve a high degree of magnetic hardening [4]. In another study on pulsethermal processing of an NdFeB-based nanocomposite magnet utilizing high-density plasma arc lamp technology, annealing time as short as 0.5 s initiates the crystallization transition from an amorphous phase to magnetic nanocomposite, while prolonged processing is required for optimization of magnetic hardening in the ribbons [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, substitution of Dy for Nd in Nd 2 Fe 14 B increases coercivity through its high magneto-crystalline anisotropy but reduces the net magnetization through the Dy's antiferromagnetic coupling to the Fe, thus causing loss in remanence and energy product. The other is heat treatment to form nanocomposite structures such as Nd 2 Fe 14 B/a-Fe with grain sizes less than 10 nm and volume fraction of a-Fe under 0.4 [3][4][5]. Here an exchange interaction at nanoscale between magnetically hard phase with high anisotropy and soft phase with high magnetization increases the magnetization significantly above that of the hard phase leading to the potential energy product as high as 100 MGOe at room temperature and 30 MGOe at 450 1C [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the PTP-processed samples apparently have very large grain sizes (100-200 nm), signifi cantly larger than those (30-90 nm) of conventional furnace-annealed samples and those (20-50 nm) of RTP samples. 15 It seems that a high-pulsecurrent-processed sample has a more clear grain interface than low-currentprocessed samples. The latter has a non-uniform size distribution, which may account for the large step on the loop although relatively large coercivity was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…14 A recent investigation revealed that heating time as short as 1 s results in a high degree of magnetic hardening and complete crystallization in amorphous NdFeB ribbons. 15 This interesting fi nding leads to a key question: how fast can magnetic hardening be realized in a given magnetic material? This paper reports preliminary results achieved using pulse-thermal processing (PTP) of an NdFeB-based nanocomposite magnet.…”
Section: Nanocrystalline Materials Possess Physical and Chemical Propmentioning
confidence: 99%